Relevancy of Banking Services Costs: The Case of Less Developed Regions in Jordan - Al Sawalqa, Fawzi; Aliqah, Khaled Abu (Asian Economic and Financial Review, 2013)
The current study utilises the quantitative methodology research approach to achieve two objectives. These include; firstly, to identify the main acceptance banking services at Tafila governorate, and secondly, to identify the nature of the relationship between the cost of different banking services and their acceptance by customers. The results revealed that the most five accepted services include; ATM withdrawal service, balance checking using ATM, counter deposit service, fund transferring using counter, request for account statement using ATM respectively. When banking services taken as categories, the result reveal that the traditional-counter banking services still occupied the first place among the customer of commercial banks located at Tafila region. These results indicate that customers of such region still give a big deal to the security and give no trust to the electronic tools to perform such services. In respect to the effect of costs of the three main banking services (i.e. e-banking services, traditional-counter banking services and lending services) and their acceptance by customers. The results indicate that the cost of each category of services does contribute significantly toward the acceptance of such category of services. This unexpected result was justified based on many factors such as the financial behaviour of customers and their income level.